PENGARUH PEMBERIAN SILASE KULIT PISANG TERHADAP PERFORMA DAN KONVERSI RANSUM PADA DOMBA EKOR TIPIS - Maliya, Mirwa Siti; Adhianto, Kusuma; Liman, Liman; Husni, Ali (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2025)
This research aims to determine the best treatment for giving banana peel silage on body weight gain, ration consumption and ration conversion. This research was carried out in December 2023 ̶ February 2024 located at the Animal Husbandry Department, Faculty of Agriculture, Lampung University, Bandar Lampung. This research was carried out using a Randomized Block Design (RAK) consisting of 3 treatments and 5 replications, using 15 thin-tailed sheep. The treatment used is P0: 50% concentrate + 50% tebon silage; P1: 50% concentrate + 35% tebon silage + 15% banana peel silage; P2: 50% concentrate + 20% corn stalks silage + 30% banana peel silage. The data obtained were analyzed using Analysis of Variance (ANOVA). The results of the research on daily body weight gain were (P0 50,57±29,78; P1 90,19±11,03; P2 62,64±32,31) gr/day, on ration consumption of (P0 1118,18±71,06; P1 1252,47±241,82; P2 1322,82±138,50) gr/day, and at ration conversion of (P0 25,38±14,46; P1 14±2,71; P2 25,89±14,69). Providing banana peel silage in treatment P1 had the best effect on daily body weight gain and feed consumption. The P2 treatment had the best effect on feed conversion.